Extended spectrum beta‐lactamase producing Shiga‐toxin producing‐Escherichia coli in piglets, humans and water sources in North East region of India. (1st November 2019) - Puii, L.H.; Dutta, T.K.; Roychoudhury, P.; Kylla, H.; Chakraborty, S.; Mandakini, R.; Kawlni, L.; Samanta, I.; Bandopaddhay, S.; Singh, S.B.
Abstract: Extended spectrum β‐lactamases (ESBL) producing Shiga toxin producing E. coli (STEC) are posing a constant threat to public health throughout the world leading to serious infections and raising key therapeutic issues. A total of 219 fecal samples were collected from piglets with diarrheoa, pig farmers and water sources in North East India; and were processed for isolation of Escherichia coli . The isolates were screened for antimicrobial resistance and suspected isolates for ESBLs production by double‐disk synergy test (DDST). Escherichia coli isolates positive for DDST were subjected for detection of selected ESBL/beta‐lactamase genes and virulence associated genes by PCR. By DDST, 337 (67·94%) E. coli isolates were detected as ESBLs producer, of which 211 (66·98%), 117 (70·91%) and 9 (56·25%) isolates were from piglets, humans and water sources respectively. A total of 64 (12·90%) isolates were recorded as STEC, of which 48 (9·68%), 6 (1·21%) and 10 (2·02%) were from human, piglets and water respectively. Majority of the STEC isolates (64·06%) possessed multiple virulence genes, of which 59·38% also harboured ESBL/beta‐lactamase genes with 32·81% STEC isolates being positive for multiple ESBL/beta‐lactamase genes. Significance and Impact of the Study: Multidrug resistant (MDR) enteric bacteria are global concern. Association of MDR traits in STEC isolates are another rising issue in human and animal health perspective. The interaction of such organisms among the human, domestic animals and adjoining water sources require to be analysed systematically. The present study exhibited the possible transmission of MDR‐STEC among the human, domestic animals and water sources in the North eastern states of India. To the best of our knowledge, this is the first report of such kind in India.